Diplomasi Publik Cina terhadap Indonesia dalam Festival Kue Bulan Tahun 2023 - Ramaldy Krisna Indradipradana; Bevita Sari; Muhammad Fauzi Abdul Rachman (Jurnal Syntax Admiration, 2024)
The Mooncake Festival is one of China's public diplomacies through cultural activities towards Indonesia. On September 27, 2023, the Chinese Government, through its Ambassador in Indonesia, held a Mooncake Festival with the theme "Celebrating the Mid-Autumn Festival with Full Flower and Full Moon". This festival is momentum for the Chinese Government to introduce the Mooncake Festival as one of the biggest celebrations in Chinese culture to the Indonesian people. This study aims to examine China's public diplomacy efforts towards Indonesia through the 2023 Mooncake Festival. This study uses a qualitative method, with primary and secondary data sources and qualitative descriptive analysis techniques. By utilizing the concept of public diplomacy from Ingrid D'Hooge, the conclusion of this study is the implementation of China's public diplomacy towards Indonesia through the 2023 Mooncake Festival involves many non-state actors and developing and launching strategies that focus on its culture by introducing Chinese culture to Indonesia. Not only that, China also uses publication media to implement China's public diplomacy toward Indonesia's success through the 2023 Mooncake Festival.